Implementasi Kerjasama Sister Province Antar Daerah Istimewa Yogyakarta Dan Victoria Melalui Melbourne Symphony Orchestra (MSO) - Simanjuntak, Stefhani Krisna Mei; Hadiwijoyo, Suryo Sakti; Simanjuntak, Triesanto Romulo (Administraus, 2024)
This research to evaluate the implementation of the sister province cooperation between the Special Region of Yogyakarta (DIY) and Victoria, Australia, through the Melbourne Symphony Orchestra (MSO), which began in 2015. The main focus of this cooperation is to enhance access to music education and develop arts infrastructure in DIY. The research employs a descriptive qualitative method, collecting primary data through in-depth interviews and secondary data from relevant documents. The findings indicate that this cooperation has successfully carried out various activities, including cultural exchanges, workshops, and collaborative concerts, with the Youth Music Camp program being a key initiative involving young musicians and resulting in joint performances. Additionally, the study identifies the crucial role of local government as a facilitator in establishing this cooperation. Overall, the research confirms that this partnership not only strengthens interregional relations but also significantly contributes to the development of arts and culture in the Special Region of Yogyakarta.